Internalization of Islamic Educational Values in Social Mediation Practices: A Case Study of Balinuraga Village, South Lampung - Basri, Basri (Madania: Jurnal Kajian Keislaman, 2025)
The conflict resolution method employed by the Prophet Muhammad SAW in fostering peace remains effective to this day in addressing disputes between groups. As the primary actor, mediator, and participant in conflicts, the Prophet Muhammad SAW exemplified a solution-oriented and humanistic approach. His methodology emphasized problem-solving by ensuring justice and balancing the interests of all parties involved. This study examines the extent to which the conflict resolution approach of the Prophet Muhammad SAW was implemented in promoting peace in Balinuraga Village, Way Panji District, South Lampung, following an inter-group conflict. A key reference during the Prophet’s era was the Medina Charter, which enshrines foundational principles for coexistence, including justice, protection of human rights, interfaith tolerance, and equality before the law irrespective of ethnicity, religion, or social status. Moreover, the spirit of pluralism introduced by the Prophet Muhammad SAW through the Medina Charter serves as a crucial basis for constructing a peaceful and inclusive society. In contemporary contexts, pluralism can only thrive when underpinned by principles of tolerance, anti-discrimination, legal fairness, and non-violence. Exclusive mindsets and attitudes often incite provocations that lead to communal and separatist conflicts, thus necessitating a counterbalance of solidarity and empathy, particularly towards vulnerable groups or victims of violence. Penelitian ini bertujuan untuk mengkaji sejauh mana metode resolusi konflik yang dipraktikkan oleh Rasulullah SAW dapat diimplementasikan dalam menciptakan perdamaian di Desa Balinuraga, Kecamatan Way Panji, Lampung Selatan, pascakonflik antarkelompok. Fokus utama penelitian ini adalah menganalisis relevansi prinsip-prinsip perdamaian Rasulullah SAW, khususnya yang tercermin dalam Piagam Madinah, dalam konteks sosial dan kultural masyarakat setempat. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi terhadap tokoh masyarakat, aparat desa, dan korban konflik. Analisis dilakukan secara deskriptif-analitik untuk mengidentifikasi kesesuaian nilai-nilai resolusi konflik Rasulullah SAW dengan praktik lokal dalam membangun harmoni pascakonflik. Hasil penelitian menunjukkan bahwa nilai-nilai dalam Piagam Madinah seperti keadilan, perlindungan hak, toleransi antaragama, serta persamaan di hadapan hukum menjadi inspirasi dalam proses rekonsiliasi di Balinuraga. Pendekatan inklusif dan humanis yang menekankan keadilan restoratif terbukti mampu meredam konflik lanjutan dan membangun kembali kepercayaan antarkelompok. Penelitian ini berkontribusi pada pengembangan model resolusi konflik berbasis nilai-nilai Islam yang kontekstual, serta memperkuat pentingnya semangat pluralisme, anti-diskriminasi, dan solidaritas sosial dalam membangun perdamaian berkelanjutan di masyarakat multikultural.